Driving and Inhibiting Factors for Economic Empowerment and Entrepreneurship Around Muhammadiyah Charity in West Sumbawa - Ibrahim, Ibrahim; Mintasrihardi, Mintasrihardi (International Journal for Disaster and Development Interface, 2024)
The characteristics of the community in economic empowerment and entrepreneurship are still low. The purpose of this study was to analyze the driving and inhibiting factors of economic empowerment and entrepreneurship around the Muhammadiyah charity business in Taliwang, West Sumbawa Regency. The research method used is survey research. Implementation of determining the sample of respondents using proportional sampling technique. Analysis using crosstabs. The results showed that the driving factors included: 1) motivation 2) Human Resources and 3) Technology and inhibiting factors including: 1) budget, 2) facilities and infrastructure and 3) mobilization participation. The driving and inhibiting factors have different classification levels. This research serves as a basis for developing West Sumbawa Muhammadiyah Regional Leadership by forming a team of drivers for economic empowerment and entrepreneurship around Muhammadiyah's charitable endeavors.